Forty-Eight Week Outcomes of a Site-Randomized Trial of Combined Cognitive Behavioral Therapy and Medication Management Algorithm for Treatment of Depression Among Youth With HIV in the United States. (1st November 2022) - Brown, Larry K.; Baltrusaitis, Kristin; Kennard, Betsy D.; Emslie, Graham J.; Chernoff, Miriam; Buisson, Sarah; Lypen, Kathryn; Whiteley, Laura B.; Traite, Shirley; Krotje, Chelsea; Knowles, Kevin; Townley, Ellen; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Studies suggest that manualized, measurement-guided, depression treatment is more efficacious than usual care but impact can wane. Our study among youth with HIV (YWH), aged 12–24 years at US clinical research sites in the International Maternal Pediatric Adolescent AIDS Clinical Trials Network, found a significant reduction in depressive symptoms among YWH who received a manualized, measurement-guided treatment. This paper reports outcomes up to 24 weeks after the intervention. Methods: Eligibility included diagnosis of ongoing nonpsychotic depression. Using restricted randomization, sites were assigned to either combination cognitive behavioral therapy and medication management algorithm tailored for YWH or to enhanced standard of care, which provided psychotherapy and medication management. Site-level mean Quick Inventory for Depression Symptomatology Self-Report (QIDS-SR) scores and proportion of youth with treatment response (>50% decrease from baseline) and remission (QIDS-SR ≤ 5) were compared across arms using t tests. Results: Thirteen sites enrolled 156 YWH, with baseline demographic factors, depression severity, and HIV disease status comparable across arms. At week 36, the site-level mean proportions of youth with a treatment response and remission were greater at combination cognitive behavioral therapy and medication management algorithm sites (52.0% vs. 18.8%, P = 0.02; 37.9% vs. 19.4%, P = 0.05), and the mean QIDS-SR was lower (7.45 vs. 9.75, P = 0.05). At week 48, the site-level mean proportion with a treatment response remained significantly greater (58.7% vs. 33.4%, P = 0.047). Conclusions: The impact of manualized, measurement-guided cognitive behavioral therapy and medication management algorithm tailored for YWH that was efficacious at week 24 continued to be evident at weeks 36 and 48.